First records of actual and fossil stephadiscus outside Patagonia, and description of a new Amazonian species (Mollusca: Pulmonata: Charopidae) - Miquel, Sergio Eduardo (2011)
An extension of both temporal and spatial range of Stephadiscus is provided, together with the description of the first Amazonian species (recorded from Peru) and the first Holocene fossils (found in Chile). The new species, S. madrediosensis, was recorded in the Peruvian department Madre de Dios. The first Chilean fossils of the genus, which would have lived in more humid environmental conditions than at present, are recorded from the region of Los Vilos (Choapa province), for the late Holocene. Both findings show that thegenus Stephadiscus has been distributed in the past and at present beyond the limits of the Patagonian area.